Sound Absorption Properties of Oil Palm Empty Fruit Bunch Cement Boards (EFBCB) Based on Outdoor Exposure - Mohd Adnan, Nurul Syafika; Abu Bakar, Hasniza (Recent Trends in Civil Engineering and Built Environment, 2024)
Many researchers have been conducted study to optimize the use of natural fibres as sound insulation materials. Due to the problem of major wastes of oil palm, the use of natural fibers including palm oil corp waste fibres for the purpose of building materials have been introduced. Therefore, this study focuses on the effect of outdoor condition towards sound absorption performance of Empty Fruit Bunch Cement Board (EFBCB). Measurement of sound absorption coefficient is done using impedance tube for low and high frequency according to BS EN ISO 10534. The result shows that the treated sample which is not exposed to outdoor with 0.987 of sound absorption coefficient at low frequency is the higher result for untreated sample. For high frequency, the treated sample which exposed to outdoor with 0.859 of sound absorption is the higher result. It can be concluded that outdoor exposure condition effect the absorption capabilities of EFBCB.